A Comparative Study on the Design Spectra Defined by Several Codes of Practice on RC Building Located in Baghdad City - Jarallah, Husain Khalaf; Taki, Zahir Noori M. (Al-Nahrain Journal for Engineering Sciences, 2017)
This paper studies the effect of different design spectral response acceleration parameters as suggested by the uniform building code (UBC), unified facilities criteria (UFC), and Iraqi seismic code(1997) (ISC 97) on the seismic response of reinforced concrete multi-story framed building located in Baghdad city, Iraq. These parameters are: (a) spectral response accelerations Ss, at short periods, and S1 at a 1-second period in accordance with international building code (IBC), (b) seismic zone factor (Z) according to UBC, (c) Seismic hazard zoning coefficient (Z) according to ISC 97. In this paper, first, the elastic seismic responses for significant modes of vibration for chosen building under design response spectrum that obtained from the above mentioned codes are calculated, and then a comparison was made among different design spectral response acceleration parameters. The intent of this study is to review the seismic provisions of the current edition of Iraqi seismic code (1997) to determine whether it provides an equivalent level of safety to that contained in other international codes. Design base shears, lateral seismic forces, inter story drifts, response spectrum modal, effective seismic modification, floors acceleration and story shears are comparatively presented.